(untitled) (Eurasian Medical Research Periodical, 2024)
In the development of chronic obstructive pulmonary disease in children, the premorbid background of the child and the state of the general reactivity of the body play an important role. Among the endogenous factors that determine the degree of likelihood of developing this disease, great importance is attached to immunological processes. The use of various means aimed at enhancing immunity significantly increases the effectiveness of treatment. In this regard, we studied the state of immunity in sick children with chronic obstructive pulmonary disease. The indicators of cellular and humoral immunity were studied in chronic obstructive pulmonary disease in children. The studies carried out confirm the significant pathogenetic significance of immunological deficiency in the course of chronic obstructive pulmonary disease in children and indicate the need for its correction